Bilaterally Located Bochdalek Hernia - Kirkil, Gamze; Muz, Mehmet Hamdi; Kocakoc, Ercan (Aves, 2009)
Bochdalek hernia is a type of congenital diaphragmatic hernia (CDH) that typically presents in childhood, but may rarely be detected in adults. Most cases are asymptomatic and diagnosed incidentally. Hernias are often located on the leftside, while bilateral location is rare. We present a 75-year-old man in whom bilaterally Bochdalek hernia was detected incidentally.
Keywords: Bochdalek hernia; congenital diaphragmatic hernia; spiral computed tomography